A conserved ARF–DNA interface underlies auxin-triggered transcriptional response - Juriaan Rienstra; Vanessa Polet Carrillo-Carrasco; Martijn de Roij; Jorge Hernandez-Garcia; Dolf Weijers (Proceedings of the National Academy of Sciences, 2025)
Auxin Response Factor (ARF) plant transcription factors are the key effectors in auxin signaling. Their DNA-Binding Domain (DBD) contains a B3 domain that allows base-specific interactions with Auxin Response Elements (AuxREs) in DNA target sites. Land plants encode three phylogenetically distinct ARF classes: the closely related A- and B-classes have overlapping DNA binding properties, contrasting with the different DNA-binding properties of the divergent C-class ARFs. ARF DNA-binding divergence likely occurred early in the evolution of the gene family, but the molecular determinants underlying it remain unclear. Here, we show that the B3 DNA-binding residues are deeply conserved in ARFs, and variability within these is only present in tracheophytes, correlating with greatly expanded ARF families. Using the liverwort Marchantia polymorpha , we confirm the essential role of conserved DNA-contacting residues for ARF function. We further show that ARF B3–AuxRE interfaces are not mutation-tolerant, suggesting low evolvability that has led to the conservation of the B3–DNA interface between ARF classes. Our data support the almost complete interchangeability between A/B-class ARF B3 by performing interspecies domain swaps in M. polymorpha , even between ARF lineages that diverged over half a billion years ago. Our analysis further suggests that C-class ARF DNA-binding specificity diverged early during ARF evolution in a common streptophyte ancestor, followed by strong selection in A and B-class ARFs as part of a competition-based auxin response system.